1995
DOI: 10.1016/0896-6273(95)90331-3
|View full text |Cite
|
Sign up to set email alerts
|

A c-jun dominant negative mutant protects sympathetic neurons against programmed cell death

Abstract: Sympathetic neurons depend on nerve growth factor (NGF) for survival and die by apoptosis in its absence. We have investigated the pattern of expression of the Jun and Fos family of transcription factors in dying sympathetic neurons using antibodies specific for each family member. When sympathetic neurons are deprived of NGF, the level of c-Jun protein significantly increases, whereas the levels of the other members of the Jun and Fos family remain relatively constant. c-Jun also becomes more phosphorylated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
623
6
3

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 778 publications
(693 citation statements)
references
References 66 publications
61
623
6
3
Order By: Relevance
“…This effect is specific to c-jun as transfection of cjun into the c-jun À/À cell line restores its endogenous activity, and which results in a phenotype similar to that of parental (wild-type (wt)) cells. The role of c-jun in apoptosis has been described in other cell lines, such as PC12 cells, which undergo apoptosis following NGF withdrawal in a c-jun-dependent manner (Ham et al, 1995). In agreement with these results, constitutive expression of c-jun in NIH3T3 cells induces apoptosis upon serum deprivation (Ham et al, 1995;Bossy et al, 1997).…”
Section: Introductionmentioning
confidence: 59%
“…This effect is specific to c-jun as transfection of cjun into the c-jun À/À cell line restores its endogenous activity, and which results in a phenotype similar to that of parental (wild-type (wt)) cells. The role of c-jun in apoptosis has been described in other cell lines, such as PC12 cells, which undergo apoptosis following NGF withdrawal in a c-jun-dependent manner (Ham et al, 1995). In agreement with these results, constitutive expression of c-jun in NIH3T3 cells induces apoptosis upon serum deprivation (Ham et al, 1995;Bossy et al, 1997).…”
Section: Introductionmentioning
confidence: 59%
“…Initial studies using PC12 cells and sympathetic neurons showed that inhibition of c-Jun activity, either by microinjection of antibodies against c-Jun or expression of dominant negative mutant forms of the protein protects the cells from nerve growth factor (NGF) withdrawal-induced apoptosis (Estus et al, 1994;Ham et al, 1995;Xia et al, 1995). Furthermore, ectopic expression of c-Jun is su cient to drive sympathetic neurons into apoptosis in the absence of external stimuli (Ham et al, 1995). Similarly, overexpression c-Jun was shown to induce apoptosis in 3T3 ®broblasts (Bossy-Wetzel et al, 1997).…”
Section: Jun As a Mediator Of Apoptosismentioning
confidence: 99%
“…One of the first regulated genes to be identified was the basic/leucine zipper transcription factor c-Jun, a member of the AP-1 family. The level of the c-jun mRNA and c-Jun protein increases rapidly in sympathetic neurons after NGF withdrawal, and microinjection of neutralizing antibodies against c-Jun or expression of a c-Jun dominant-negative mutant protects sympathetic neurons against NGF withdrawal-induced death, 4,5 as does conditional knockout of the c-jun gene in sympathetic neurons isolated from mice with a floxed c-jun gene. 6 These observations supported the idea that NGF withdrawal-induced death involves the transcriptional induction of genes that activate the cell death programme.…”
Section: Ngf Withdrawal-induced Death Requires Transcription and Invomentioning
confidence: 99%